Unbound spirit : letters of Flora Belle Jan - Jan, Flora Belle, 1906-1950 (University of Illinois Press, 2009)
This volume collects the letters written over a thirty-year period by a second generation Chinese American woman, Flora Belle Jan (1906-50). Born in California to immigrant parents and educated at Berkeley and the University of Chicago, Jan raised three children with her husband Charles Wang and worked as a journalist in both the United States and China. Written during the years 1918-48, these letters offer unique insight into the social and political situation of educated, middle-class, professional Chinese American women in the early twentieth century. --From publisher's description.